Eucalyptus Globulus Ethanol Extract Mitigates Formalin-Induced Acute Cardiotoxicity by Lowering Uric Acid and Lactate Dehydrogenase in Male Swiss Mice - Dangana, Elizabeth Ojochebo; Caleb, Jonah Achile; Ozovehe, Suleiman Haruna; Idowu Olumorin, Owemidu; Odoma, Saidi; Nafiu, Negedu Muhammed; Taiwo Abayomi, Abraham; Ogunkolo, Francis Olukoya (The Pharmaceutical and Chemical Journal, 2020)
Background: E.globulus is a medicinal plant which has been shown to possess and exhibit various beneficial properties like anti-inflammatory, anticancer, antibacterial, antiseptic and astringent. Aim: To investigate the cardioprotective properties of E. globulus against formalin-induced acute cardiotoxicity in male Swiss mice and to determine the possible mechanism of its cardioprotective effects. Materials and Methods: Thirty animals were randomly selected into six groups of five animals each as follows; Control group received distil water, extract group (500mg/kg p.o daily), formalin group (20μl/kg i.p) formalin+pro+extract (propranolol, 40mg/kg with E.globulus extract 500mg/kg p.o daily), formalin+gli+extract group (glibenclamide, 8mg/kg with E.globulus extract 500mg/kg p.o daily) formalin+nife+extract group (nifedipine, 10mg/kg with E.globulus extract 500mg/kg p.o daily). The treatment period lasted for two weeks. The mechanism of action was investigated using adrenergic, L type voltage gated calcium channel, and ATP sensitive K+ channel blockers. Results: Cardiotoxicity was assessed by measuring cardiac uric acid, lactate dehydrogenase, urea, and some haematological indices. Treatment with E. globulus (500mg/kg) significantly (p<0.05) decreased the levels of cardiac uric acid and lactate dehydrogenase activity. Conclusion: These results suggest that E. globulus has the potential in preventing the cardiotoxic effects induced by formalin possibly through a mechanism that may involve the adrenergic system and the L-Type Voltage gated Calcium channel.
Keywords: Formalin; E.globulus; Uric acid and lactate dehydrogenase